FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS KESEMBUHAN PENDERITA TUBERKULOSIS PARU - Dhina Nurlita Niviasari; Lintang Dian Saraswati; Martini Martini (Jurnal Kesehatan Masyarakat (Undip), 2017)
Pulmonary tuberculosis patients cure rate is an indicator of the national programme to combat tuberculosis disease in an area. The target for national cure rate is 85%. Cure rate in Semarang from 2010 to 2013 experienced fluctuative trend and the latest in 2013 riched 61%. The purpose of this research was  to know several factors associated with cure status of pulmonary tuberculosis patients  after undergone treatment during six months. This research used observational analytic study with case control design study. This case control study used data which was taken from cases that taken from January 2013-March 2015. This cases consist of 36 patients who were cured and 36 others who were not cured. The sample was selected by using purposive sampling. Bivariat analysis result proved the existence of relationship between patients who are above 45 years old (OR = 5.1; 95% CI 1,379-19,106), regularity of treatment (OR = 7.7; 95% CI 2,452-24,496), and the presence of another disease (OR= 7.0; 95% CI 1,799-27,236) with cure status of pulmonary tuberculosis patients. Based on these research we suggest the availability of health workers who are responsible to monitor the uptake of the drugs and the availability of form for PMO to monitor the regularity of patients in taking medication.